PENGEMBANGAN BAHAN AJAR IPS AUTENTIK: STUDI VALIDASI LEMBAR KERJA PESERTA DIDIK BERBASIS LAPANGAN DI LINGKUNGAN RUSTIC MARKET PACET - Muhammad Sendi Pegriyanto; Ahmad Fian Saputra; Riska Agnes Ristanti; Khanifa Maria Qurrota A’yun; Alina Dewi Churun Aini; Nayalla Nanda Anwari; Muhammad Ilyas Marzuqi (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
The conventional LKPD structure that lacks contextual exploration is the background to this research to answer the demands of the Independent Curriculum Phase D. This research focuses on the development of authentic teaching materials in the form of field-based Electronic Student Worksheets (E-LKPD) by highlighting the local economic potential in the Rustic Market Pacet area. The method used is Research-Based Instructional Design (RBID) which is adjusted through the stages of curriculum analysis, prototype design, flipbook-based digital development, and quantitative descriptive evaluation using the Aiken's V index. The research findings show that this 19-page self-guided product obtained an Aiken's V index score of 0.90 from material experts and 0.92 from media experts, thus entering the "Very Good" category. The practicality test by social studies teachers resulted in an average score of 0.89, proving this media is very practical in facilitating the delivery of real phenomena interactively via mobile phones or laptops without geographical barriers. The integration of learning video features and QR Code-based visual mapping has proven effective in facilitating the seven components of Contextual Teaching and Learning (CTL). The main conclusion confirms that this Contextual Geography E-LKPD is very suitable for use as an innovative instrument to improve students' critical thinking skills in understanding the Environmental Economic Potential material through meaningful independent learning experiences. ABSTRAK Struktur LKPD konvensional yang minim eksplorasi kontekstual melatarbelakangi dilakukannya riset ini guna menjawab tuntutan Kurikulum Merdeka Fase D. Penelitian ini berfokus pada pengembangan bahan ajar autentik berupa Elektronik Lembar Kerja Peserta Didik (E-LKPD) berbasis lapangan dengan mengangkat potensi ekonomi lokal di kawasan Rustic Market Pacet. Metode yang digunakan adalah Research-Based Instructional Design (RBID) yang disesuaikan melalui tahapan analisis kurikulum, perancangan prototipe, pengembangan digital berbasis flipbook, serta evaluasi deskriptif kuantitatif menggunakan indeks Aiken’s V. Temuan penelitian menunjukkan bahwa produk bimbingan mandiri setebal 19 halaman ini memperoleh nilai indeks Aiken’s V sebesar 0,90 dari pakar materi dan 0,92 dari pakar media, sehingga masuk kategori "Sangat Baik". Uji kepraktisan oleh guru IPS menghasilkan nilai rata-rata 0,89, membuktikan media ini sangat praktis mempermudah penyampaian fenomena riil secara interaktif lewat ponsel maupun laptop tanpa hambatan geografis. Integrasi fitur video pembelajaran dan pemetaan visual berbasis QR Code terbukti efektif memfasilitasi tujuh komponen Contextual Teaching and Learning (CTL). Simpulan utama menegaskan bahwa E-LKPD Geografi Kontekstual ini sangat layak digunakan sebagai instrumen inovatif untuk meningkatkan kemampuan berpikir kritis siswa dalam memahami materi Potensi Ekonomi Lingkungan melalui pengalaman belajar mandiri yang bermakna.